Oral cavity manifestations by COVID-19 infections: a review - Swain, Santosh Kumar; Debta, Priyanka; Sahu, Ansuman; Lenka, Smarita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Coronavirus disease 2019 (COVID-19) is a threat to the global health caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The lungs are the primary site of infection in COVID-19 patient and the symptoms ranges from mild flu like manifestations to fulminant pneumonia and respiratory failure. COVID-19 infection also significantly affects the oral cavity and salivary glands with oral mucosal manifestations. Other than airway manifestations, COVID-19 patients are presenting with oral cavity lesions such as aphthous like ulcers, glossitis, oral mucositis or stomatitis, oral candidiasis and herpetic recurrences. These oral lesions are often associated with immunocompromised patients and elderly age. Direct involvement of the SARS-CoV-2 virus for development of oral ulcers remains uncertain. The salivary gland related symptoms and taste disturbances are highly common in COVID-19 patients. In COVID-19 patient, certain presentations like ulcers or blisters or diffuse reddish lesions affect both keratinized and non-keratinized tissues of the oral cavity. These lesions are found in palate, lip mucosa, buccal mucosa and tongue. The ulceration and blisters of the oral cavity are more often seen. There is still a gap of knowledge related to the oral manifestations of the COVID-19 infections and its impact on the oral cavity. This review article discussed the details of the oral cavity lesions in COVID-19 patients.